Therapeutic efficacy and toxicity of bolus application of chemotherapy protocol in the treatment of metastatic colorectal cancer - Ibrahim Šišić; Belma Pojskić; Alma Mekić-Abazović; Vladimir Kovčin (Medicinski glasnik, 2015)
Aim: To compare efficacy and toxicity of bolus application of chemotherapy protocol, oxaliplatin, fluorouracil (bolus), leucovorin (folfox) between two groups of patients in the therapy of metastatic colorectal carcinoma (mCRC). Methods: A total of 63 patients were treated for mCRC in the period January 2009 - January 2010 at the Department of Oncology of the Cantonal Hospital Zenica, Bosnia and Herzegovina (first group, 30 patients) and at the Department of Oncology of the Clinical Hospital Centre Bežanijska kosa in Belgrade, Serbia, in the period January 2005 - January 2006 (second group, 33 patients). The patients were treated according the same protocol, i.v. bolus infusion, but in different day intervals (D), 1, 8, 15/28 days or D1-D5/28 days, respectively. In all patients the following factors were analyzed: tumor response, overall survival (OS), progression free survival, hematological and non-hematological toxicity . Results: Colon was the primary localization in almost two thirds of patients. There was no statistically significant difference between the groups according to the age, hematological and non-hematological toxicity, as well as in achieved OS. Progression free survival expressed in months was in average 5 months though with a large range between minimal and maximal survival time. Conclusion: Both groups have shown equivalent efficacy to applied chemotherapy protocols. Overall survival in the two groups matched data from the literature. Further research should confirm success of the combination of chemotherapy protocols and their combination with the biological therapy.
Keywords: oxaliplatin; therapeutic response; overall survival; toxicity